Characterization of new users of cilostazol in the UK, Spain, Sweden, and Germany. Issue 6 (30th January 2017) - Castellsague, Jordi; Perez‐Gutthann, Susana; Calingaert, Brian; Bui, Christine; Varas‐Lorenzo, Cristina; Arana, Alejandro; Prados‐Torres, Alexandra; Poblador‐Plou, Beatriz; Gonzalez‐Rubio, Francisca; Giner‐Soriano, Maria; Roso‐Llorach, Albert; Linder, Marie; et al.
Abstract: Purpose: To describe the characteristics of new users of cilostazol in Europe with the aim to support the evaluation of its benefit/risk as used in regular clinical practice before the implementation of labeling changes recommended by the European Medicines Agency. Methods: New users of cilostazol were identified in populations enrolled in five European health automated databases in the UK (The Health Improvement Network [THIN]), Spain (EpiChron cohort and Information System for the Improvement of Research in Primary Care [SIDIAP]), Sweden (National Registers), and Germany (German Pharmacoepidemiological Research Database [GePaRD]) between 2002 and 2012. New users were characterized according to the prevalence of cardiovascular disease and other comorbidities, concurrent use of interacting medications, new contraindications, duration of use, and potential off‐label prescribing. Results: We identified 22 593 new users of cilostazol. The median age was between 68.0 (THIN) and 73.7 (Sweden) years. More than 78% of users had concomitant cardiovascular disease, and between 78.8% (GePaRD) and 91.6% (THIN) were treated with interacting medications. Prevalence of new cardiovascular contraindications ranged from 1.5% (THIN) to 11.6% (GePaRD), and concurrent use of two or more antiplatelet drugs ranged from 6.3% (SIDIAP) to 13.5% (EpiChron cohort). Between 39.4% (Sweden) and 52.9% (THIN) of users discontinued cilostazol in the first 3 months. Between 41.0% (SIDIAP) and 93.4% (THIN) were considered to have received cilostazol according to the European Medicines Agency labeling. Conclusions: In this collaborative European study, most cilostazol users were elderly patients with a high prevalence of cardiovascular diseases and other comorbidity and concurrent use of interacting drugs, indicating that this is a vulnerable population at high risk of complications, especially cardiovascular events. © 2017 The Authors. Pharmacoepidemiology and Drug Safety Published by John Wiley & Sons Ltd.